ACHIEVEMENT STUDENT SUPPORT SYSTEM USING WEIGHTED PRODUCT METHOD - Rahayu, Dewi; Idris, Muhammad (JLCEdu (Journal of Learning and Character Education), 2022)
Constitution of the Republic of Indonesia No 12 of 2012 that higher education in part of the national education system has a strategic role in educating the life of the nation. Students are people who try to develop themselves through the educational process on a particular path, level and type of education. The Weighted Product method is chosen because the method of completion uses multiplication to connect the attribute value, where the value must be raised with the value of the attribute weight in question. Criteria that have been determined include average value, discipline, attendance, extracurricular, and Non-Academic. The results of this study there are 6 alternatives, that A2 alternative with the value 0.145790734 as students with the lowest value and alternative A3 0.212196782 as students with the best value.